Development and crystal structures of a potent second-generation dual degrader of BCL-2 and BCL-xL - Digant Nayak; Dongwen Lv; Yaxia Yuan; Peiyi Zhang; Wanyi Hu; Anindita Nayak; Eliza A. Ruben; Zongyang Lv; Patrick Sung; Robert Hromas; Guangrong Zheng; Daohong Zhou; et al. (Nature Communications, 2024)
Abstract Overexpression of BCL-xL and BCL-2 play key roles in tumorigenesis and cancer drug resistance. Advances in PROTAC technology facilitated recent development of the first BCL-xL/BCL-2 dual degrader, 753b, a VHL-based degrader with improved potency and reduced toxicity compared to previous small molecule inhibitors. Here, we determine crystal structures of VHL/753b/BCL-xL and VHL/753b/BCL-2 ternary complexes. The two ternary complexes exhibit markedly different architectures that are accompanied by distinct networks of interactions at the VHL/753b-linker/target interfaces. The importance of these interfacial contacts is validated via functional analysis and informed subsequent rational and structure-guided design focused on the 753b linker and BCL-2/BCL-xL warhead. This results in the design of a degrader, WH244, with enhanced potency to degrade BCL-xL/BCL-2 in cells. Using biophysical assays followed by in cell activities, we are able to explain the enhanced target degradation of BCL-xL/BCL-2 in cells. Most PROTACs are empirically designed and lack structural studies, making it challenging to understand their modes of action and specificity. Our work presents a streamlined approach that combines rational design and structure-based insights backed with cell-based studies to develop effective PROTAC-based cancer therapeutics.